Impact of Ghana’s agricultural mechanization services center program - Benin, Samuel (International Food Policy Research Institute, 2014)
Use of mechanization in African agriculture has returned strongly to the development agenda, particularly following the recent high food prices crisis. Many developing country governments—including Ghana, the case study of this paper—have resumed support for agricultural mechanization, typically in the form of providing subsidies for tractor purchase and establishment of private-sector-run agricultural mechanization service centers (AMSECs). The aim of this paper is to assess the impact of Ghana’s AMSEC program on various outcomes, using data from household surveys that were conducted with 270 farmers, some of them located in areas with the AMSEC program (treatment) and others located in areas without the program (control).